Rhodium catalyzed hydrogenation reactions in aqueous micellar systems as green solvents - Schwarze, M.; Milano-Brusco, J. S.; Strempel, V.; Hamerla, T.; Wille, S.; Fischer, C.; Baumann, W.; Arlt, Wolfgang; Schomäcker, R. (RSC Advances, 2011)
The hydrogenation of itaconic acid and dimethyl itaconate is transferred from methanol to aqueous micellar solutions of several surfactants, e.g., SDS and Triton X-100, in order to facilitate the recovery of the catalyst. The reaction rate and selectivity strongly depends on the chosen surfactant and in some cases also on the surfactant concentration. In the best case the selectivity is the same as in methanol but the reaction rate is still lower because of a lower hydrogen solubility in water. Repetitive semi-batch experiments are chosen to demonstrate that high turn-over-numbers (> 1000) can be reached in aqueous micellar solutions. No notable catalyst deactivation is observed in these experiments. The performance of micellar reaction systems is controlled by the partition coefficient of the substrates between the micelles and the continuous aqueous phase which can be predicted using the Conductor-like Screening Model for Real Solvents (COSMO-RS).